Critical Discourse in Series “Dek Mai Season 2” - singthong, uraiwan; Kasemsooksamran, Cherry; Fongrit, Metta; Suthipanyo, Chomboon; klawkra, Taklaw; Lekpech, Ketsukon; ตั้งมั่น , วริศรา (Journal of MBU Humanities, 2024)
This article aims to critically analyze the discourse in the series Dek Mai Season 2 using the theories of Fairclough and Wodak. The study examines all eight episodes, employing a descriptive and analytical approach. The research findings reveal three critical discourses identified in the series 1. Power and Social Issues Discourse, divided into: 1.1) The hidden power within societal language. 1.2) The influence of mass media on social reproduction. 2. Capitalism and Power Discourse, which is divided into: 2.1) The distortion of wrongdoing. 2.2) The creation of the "other" in society. 2.3) The generation of benefits for families. 3.Gender Equality Discourse. The series Dek Mai Season 2 as a mirror reflecting discourses that shape thought, action, perspectives, and attitudes through ideology. It portrays the distribution of power through language, calling for rights, freedom, and equality, which are hidden within the social context, granting individuals the ability to live justly as a result of societal actions.